2021
DOI: 10.1021/jasms.0c00468
|View full text |Cite
|
Sign up to set email alerts
|

Influence of a Hydroxyl Group on the Deamidation and Dehydration Reactions of Protonated Asparagine-Serine Investigated by Combined Spectroscopic, Guided Ion Beam, and Theoretical Approaches

Abstract: Deamidation of asparaginyl (Asn) peptides is a spontaneous post-translational modification that plays a significant role in degenerative diseases and other biological processes under physiological conditions. In the gas phase, deamidation of protonated peptides is a major fragmentation channel upon activation by collision-induced dissociation. Here, we present a full description of the deamidation process from protonated asparagine-serine, [AsnSer+H]+, via infrared (IR) action spectroscopy and threshold collis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Indeed, tightening the vibrational frequencies below 900 cm –1 (those tagged by Gaussian 16 as potentially inaccurate) of the tight TSs by ∼25% is sufficient to bring the TCID thresholds into agreement with the theoretical values for H 2 O and CO 2 loss from (O) p-ABAH + and for H 2 O + CO 2 loss from (N)-p-ABAH + . This extent of scaling for TS frequencies is precedented in several studies conducted on the dissociation behavior of small protonated di- and tripeptides, where scaling factors of 22–32% were needed in order to quantitatively predict the relative magnitudes and energetics for competing dissociation pathways. , For BAH + , the low-frequencies for the TSs leading to H 2 O and CO 2 loss require tightening by ∼50% in order to yield quantitative agreement.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, tightening the vibrational frequencies below 900 cm –1 (those tagged by Gaussian 16 as potentially inaccurate) of the tight TSs by ∼25% is sufficient to bring the TCID thresholds into agreement with the theoretical values for H 2 O and CO 2 loss from (O) p-ABAH + and for H 2 O + CO 2 loss from (N)-p-ABAH + . This extent of scaling for TS frequencies is precedented in several studies conducted on the dissociation behavior of small protonated di- and tripeptides, where scaling factors of 22–32% were needed in order to quantitatively predict the relative magnitudes and energetics for competing dissociation pathways. , For BAH + , the low-frequencies for the TSs leading to H 2 O and CO 2 loss require tightening by ∼50% in order to yield quantitative agreement.…”
Section: Resultsmentioning
confidence: 99%
“…We subsequently found that H + Asn (Heaton & Armentrout, 2009) would deamidate, Figure 8, and in both cases, the amino succinic anhydride (aSA) product (Figure 2) formed was related to the succinimide found biologically. To examine how the C‐terminal side chain affects the kinetics and thermodynamics of the deamidation process, we have studied the sequence of protonated dipeptides of AsnXxx, where Xxx is Gly (Boles et al, 2016), Ala (Boles et al, 2018), Val (Kempkes et al, 2018), Ser (Boles et al, 2021), and Thr (Boles et al, 2019). In all of these studies, theoretical calculations were also performed to map out the reaction pathways and products.…”
Section: Protonated Dipeptides Containing Asparaginementioning
confidence: 99%
“…Numbers indicate the mass‐to‐charge ratio of all ionic species. Adapted from (Boles et al, 2016, 2018, 2019, 2021; Kempkes et al, 2018) [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Protonated Dipeptides Containing Asparaginementioning
confidence: 99%
“…Further, the level of theory that can yield the most quantitatively valid predictions, here M06-2X and B3LYP-GD3BJ with triple-ζ basis sets, is validated and allows extension to larger peptides having more complicated side chains. In this regard, our TCID approach coupled with IRMPD has been used to systematically explore the deamidation of protonated AspGly, AspAla, AspVal, AspSer, and AspThr, where deamidation of asparaginyl residues in proteins is a process believed to be associated with aging. Although as yet undemonstrated, the authors believe that systems as large as a hexapeptide are probably amenable to the detailed treatment found here, although eventually, the increasing size will lead to kinetic shifts that limit the accuracy of the thermodynamic information that can be gleaned.…”
Section: Discussionmentioning
confidence: 99%
“…explore the deamidation of protonated AspGly, 51 AspAla, 52 AspVal, 53 AspSer, 54 and AspThr, 55 where deamidation of asparaginyl residues in proteins is a process believed to be associated with aging. Although as yet undemonstrated, the authors believe that systems as large as a hexapeptide are probably amenable to the detailed treatment found here, although eventually, the increasing size will lead to kinetic shifts that limit the accuracy of the thermodynamic information that can be gleaned.…”
Section: ■ Acknowledgmentsmentioning
confidence: 99%